Diálogos a través del lente. Participación en la investigación social desde el uso del videodocumental - Torres, Andrés; Forero Hurtado, Andrea del Pilar (Facultad de Periodismo y Comunicación Social, 2018)
This text includes reflections raised from the use of documentary film in the research practices in the social field by the Semillero de Investigación en Teatro y Comunicación of the Minuto de Dios University and revolves around the participation of the people involved in these practices, of the joint construction between researchers and investigated and the possibility of registering the diverse voices of these people as part of an inclusive political commitment in the purpose of contributing from the academy to the achievement of social transformations.